Detection analysis of interior void for hot axial forging based on the interior temperature field. (25th January 2016) - Zhang, Yu-cun; Zhang, Lei-qiang; Fu, Xian-bin
Highlights: The heat transfer model of forging with void is established. The interior temperature field is measured by heat transfer model of forging with void. The change characteristics between interior temperature field and void size are analyzed. The change of interior temperature field can reflect the void size in high accuracy. Abstract: At present, detecting the interior void of hot axial forging is still a longstanding challenge in forging process. Thus the quality and pass rate of forging are badly influenced. Meanwhile, lots of resources are wasted. Aiming at the issue, a detection analysis research of interior void for hot axial forging during forging process is presented in this paper. Firstly, a two-dimensional unsteady heat transfer model is established according to the heat transfer characteristics of the forging with void. Secondly, the surface temperature field data of forging are collected by the thermal infrared imager. And these data are used as the initial condition of the heat transfer model. On the basis of it and the model, combining the information on the void size and the information on the interior measured point position, the temperature of the interior measured point is solved by using lumped parameter method and separation variable method. Then the temperature data of the interior measured points are used for analyzing the change characteristics between interior temperature field and the information on the void size. Finally, the feasibility of the detection analysis is verified according to the experimental results. These analysis results have certain practical application values. The research lays a solid theoretical and practical foundation for quantitative detection of interior void.